Unlocking Superior Stability in High-Salinity Oxygen Evolution Reaction: A Ru Stabilized NiFeOOH/Ni Anode with over 2000 h Durability - He, Jin; Sheng, Haoyun; Lin, Yichao; Gong, Bingqi; Zhao, Yayun; Tian, Ziqi; Chen, Liang (Nano-Micro Letters, 2026)
Saline water electrolysis presents a promising pathway for green hydrogen production by leveraging abundant saline water resources instead of scarce freshwater. However, the presence of highly corrosive chloride ions (Cl−) severely undermines anode durability. This instability arises from two main issues: (i) penetration of Cl− through catalyst layers to the underlying substrate and (ii) degradation of active catalytic sites due to Cl− attack. To tackle both issues simultaneously, we introduce ruthenium (Ru) ions as a dual-function stabilizing agent in NiFe-based anodes. Our results show that Ru incorporation promotes the formation of a protective surface layer enriched with Ru atoms, along with a denser NiFeOOH catalyst structure, which collectively inhibit Cl– infiltration. Moreover, atomically dispersed ruthenium (RuSA) within the NiFeOOH matrix effectively mitigates Cl–-induced corrosion of active sites. Thanks to this dual stabilization effect, the resulting RuSA-NiFeOOH/Ni anode exhibits exceptional operational stability—over 2000 h at an industrial current density of 0.5 A cm−2 in a chloride-enriched alkaline medium (1 M KOH + 2 M NaCl)—setting a new benchmark for performance under such aggressive conditions. This study establishes a robust dual stabilization strategy that significantly enhances anode stability in saline water electrolysis. Highlights: 1 A dual-function stabilizing agent in NiFe-based anodes is proposed. 2 Ru incorporation promotes the formation of a protective surface layer enriched with Ru atoms, along with a denser NiFeOOH catalyst structure. 3 RuSA-NiFeOOH/Ni anode exhibits exceptional operational stability over 2000 h at an industrial current density of 0.5 A cm−2 in a chloride-enriched alkaline medium.